THE VARIETY OF LANGUAGE SOCIAL NETWORKS AND THEIR APPLICATION IN LEARNING FOREIGN LANGUAGES - Karimova Shakhnoza Valievna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The purpose of this article is to study the educational potential of social networks in the process of learning foreign languages. Considerable attention is paid to the diversity of mobile applications and language sites for communication in the modern world. The article discusses the advantages of using these networks to solve a number of problems of teaching a foreign language.